Butane-1,2,3,4-tetraol-based amphiphilic stereoisomers for membrane protein study: importance of chirality in the linker region - Das,M; Du,Y; Mortensen,JS; Ribeiro,O; Hariharan,P; Guan,L; Loland,CJ; Kobilka,BK; Byrne,B; Chae,PS (Chemical Science, 2017)
Amphiphile selection is a crucial step in membrane protein structural and functional study. As conventional detergents have limited scope and utility, novel agents with enhanced efficacy need to be developed. Although a large number of novel agents have been reported, so far there has been no systematically designed comparative study of the protein stabilization efficacy of stereo-isomeric amphiphiles. Here we designed and prepared a novel class of stereo-isomeric amphiphiles, designated butane-1,2,3,4-tetraol-based maltosides (BTMs). These stereoisomers showed markedly different behaviour for most of the targeted membrane proteins depending on the chirality of the linker region. These findings indicate an important role for detergent stereochemistry in membrane protein stabilization. In addition, we generally observed enhanced detergent efficacy with increasing alkyl chain length, reinforcing the importance of the balance between hydrophobicity and hydrophilicity in detergent design. The stereo-isomeric difference in detergent efficacy observed provides an important design principle for the development of novel amphiphiles for membrane protein manipulation.